Respuesta :
16z + 29z = pz - v....for z
45z = pz - v
45z - pz = -v
z(45 - p) = -v
z = -v / (45 - p) <==
45z = pz - v
45z - pz = -v
z(45 - p) = -v
z = -v / (45 - p) <==
Answer:
[tex]z = \frac{-v}{45-p}[/tex]
Step-by-step explanation:
Given the equation:
[tex]16z+29z =pz-v[/tex] ....[1]
Solve for z:
Subtract pz from both sides in [1] we have;
[tex]16z+29z-pz = -v[/tex]
taking z common we have;
[tex]z(16+29-p)= -v[/tex]
Combine like terms;
[tex]z(45-p)= -v[/tex]
Divide both sides by (45-p) we have;
[tex]z = \frac{-v}{45-p}[/tex]
Therefore, the value of z is, [tex]z = \frac{-v}{45-p}[/tex]